2020
DOI: 10.1175/jhm-d-19-0029.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lateral Groundwater Flow and Subsurface Lower Boundary Conditions on Atmospheric Boundary Layer Development over Complex Terrain

Abstract: Credible soil moisture redistribution schemes are essential to meteorological models, as lower boundary moisture influences the balance of surface turbulent fluxes and atmospheric boundary layer (ABL) development. While land surface models (LSMs) have vastly improved in their hydrologic representation, several commonly held assumptions, such as free-draining lower boundary, one-dimensional moisture flux, and lack of groundwater representation, can bias the terrestrial water balance. This study explores the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 86 publications
(107 reference statements)
1
21
0
Order By: Relevance
“…Even though the reliable surface energy fluxes are constrained by facticity of EC measurements and observation limitation, our results show that the coupled WRF‐Hydro simulation very slightly and partly improves the simulated surface energy fluxes compared to the WRF atmospheric simulation. Nevertheless, we note that the groundwater lateral flow, which is not considered in this study, may functionally modulate the land surface variables via groundwater‐surface water interactions, particularly over the low‐lying areas where the groundwater table is shallow (e.g., Davison et al, 2018; Forrester & Maxwell, 2020; Maxwell et al, 2015; Sulis et al, 2017). While our model configuration approximates the hydrological processes across most of the high‐mountain terrain over this headwater area, further coupling physically‐based groundwater schemes can improve the realistic representation of hydrological processes over the mountain valley and lower reaches in the desert (e.g., Wang et al, 2014; Xie et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Even though the reliable surface energy fluxes are constrained by facticity of EC measurements and observation limitation, our results show that the coupled WRF‐Hydro simulation very slightly and partly improves the simulated surface energy fluxes compared to the WRF atmospheric simulation. Nevertheless, we note that the groundwater lateral flow, which is not considered in this study, may functionally modulate the land surface variables via groundwater‐surface water interactions, particularly over the low‐lying areas where the groundwater table is shallow (e.g., Davison et al, 2018; Forrester & Maxwell, 2020; Maxwell et al, 2015; Sulis et al, 2017). While our model configuration approximates the hydrological processes across most of the high‐mountain terrain over this headwater area, further coupling physically‐based groundwater schemes can improve the realistic representation of hydrological processes over the mountain valley and lower reaches in the desert (e.g., Wang et al, 2014; Xie et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…By comparing two coupled modelling platforms ParFlow‐WRF and TerrSysMP, Sulis et al (2017) showed the differences of heat and moisture budget in the land surface and atmospheric boundary layer, revealing the sensitivities of diurnal atmospheric processes to the lateral groundwater flow parameterization. In the case of a headwater region in the Rocky Mountain, Forrester and Maxwell (2020) reported that lateral transport of groundwater modified the coupling strength between evaporative fraction and atmospheric boundary layer in the summertime.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater connections to the atmosphere are welldocumented in modeling studies (e.g., Forrester and Maxwell, 2020). Previous studies have demonstrated connections between the atmospheric boundary layer and water table depth (e.g., Maxwell et al, 2007;Rahman et al, 2015), under land cover disturbance (e.g., Forrester et al, 2018), under extremes (e.g., Kuene et al, 2016), and due to groundwater pumping (Gilbert et al, 2017).…”
mentioning
confidence: 97%
“…Groundwater connections to the atmosphere are well documented in modeling studies (e.g. Forrester and Maxwell, 2020). Previous studies have demonstrated connections between the atmospheric boundary layer and water table depth (e.g.…”
Section: Why and How Is Groundwater Modeled At Continental To Global mentioning
confidence: 98%